WEB-BASED SCHEDULING APPLICATION AND MOTION SENSOR USING ARDUINO MEGA - nasir, januardi (Universitas Trilogi, 2021)
The purpose of this research is to find out how to make a web application that can control electronic devices in the building, find out how to make motion sensor circuits with Arduino Mega, electronic devices can be on or off, and find out which one is more efficient in using web applications and sensors. motion on the building. The results of this study indicate that the creation of a web scheduling application that can control the needs of building electronic equipment: webserver (hosting), internet connection, Ethernet shield, Arduino mega, relay module, and the use of motion sensors with Arduino Mega. which can adjust the sensitivity and time delay of signaling when there is the movement of a human object. The use of Ethernet shield and motion sensor each has advantages and disadvantages. It would be better if the two components were combined